Semi-classical molecular dynamics simulations of polariton transport in organic molecules strongly coupled to Bloch Surface Waves - Luo, Yunyi (2024)
Strong coupling has emerged as a mechanism to extend the diﬀusion length of excitons in organic semiconductors beyond their typical limits. This phenomenon manifests itself in the formation of hybrid light-matter states, known as polaritons, which arise when the interaction strength between light (e.g., cavity modes) and matter (e.g., molecular excitons) exceeds the decay rates in the system, such as cavity losses and molecular deactivation. Because of their partially photonic nature, polaritons exhibit fast and long-range propagation, resulting in enhanced transport of excitation.